SEVERE TESTICULAR ATROPHY DOES NOT AFFECT THE SUCCESS OF MICRODISSECTION TESTICULAR SPERM EXTRACTION - Bryson, Campbell F. (2013)
INTRODUCTION AND OBJECTIVES: Men with azoospermia and severe testicular atrophy may be counseled to avoid sperm retrieval due to perceived limited success. We evaluated the outcomes of microdissection testicular sperm extraction (micro-TESE) in men with severe testicular atrophy (volume ≤ 2 mL). METHODS: We reviewed the records of 1127 men with nonobstructive azoospermia who underwent micro-TESE followed by intracytoplasmic sperm injection. The men were classified into three groups based on average testicular volume (mL), ≤2, >2–10, >10. Sperm retrieval, clinical pregnancy, and live birth rates were calculated. The clinical features evaluated included age, FSH level, history of cryptorchidism, Klinefelter syndrome, varicocele, and testicular histology from diagnostic biopsy. RESULT(S): Testicular sperm were successfully retrieved in 56% of the men. Sperm retrieval rates (SRR) in men with testicular volumes of ≤ 2, >2–10, and >10 mL was 55%, 56% and 55% respectively. Of those men who had sperm retrieved, clinical pregnancy and live birth rates were similar in the three groups (55.2%, 50.0%, and 47.0%; and 47.2%, 43.0% and 42.2% respectively). Of the 106 men with average testis volume ≤ 2 mL bilaterally, men who had sperm retrieved were younger (31.1 vs. 35.2 years), and were more likely to have a history of Klinefelter syndrome (82.2% vs 55.6%) compared to those in whom sperm was not found (p < 0.05). Men in this group had a higher prevalence of Klinefelter syndrome than men with testis >2 mL (72.6% vs 5.3%, p<0.0001). Men younger than 30 years with Klinefelter syndrome had a higher SRR (81.8%) compared to men older than 30 without Klinefelter syndrome (33%, p<0.01). There was no cut-point for age beyond which sperm could not be retrieved in men with small testes. On multivariable analysis, younger age was the only preoperative factor associated with successful sperm retrieval in men with small testes (<2mL). CONCLUSION(S): Testicular volume does not affect sperm retrieval rates at our center with micro-TESE. For men with the smallest volume testes, those younger men with Klinefelter syndrome had the highest sperm retrieval rates. Severe testicular atrophy should not be a contraindication for micro-TESE.